Dilemmas of Populist Transactionalism: What are The Prospects Now for Popular Politics in Indonesia - Luky Djani, Olle Tornquist (PolGov Publishing, 2017)
Why is Indonesia by late 2016 suddenly so far from Jokowi solo model of negotiating social contracts, which even produced a president in favour of change?